In the trenches : a Russian woman soldier's story of World War I - Dubinskai͡a, Tatʹi͡ana Leonidovna, 1902-1990 (Potomac Books, an imprint of University of Nebraska Press, 2020)
"Set in Russia in the year 1916, In the Trenches is based on the true story of the author's life during WWI. Fourteen-year-old Zina runs away from home to serve on the Eastern Front as a soldier in the Russian army."--